The effect of elevated COâ‚‚ on Phaseolus vulgaris L. cv Contender,The effect of elevated carbon dioxide on Phaseolus vulgaris L. cv Contender - Mjwara, Jabulani Michael (Rhodes University, Faculty of Science, Botany Department, 1997)
The response of Phaseolus vulgaris L. cv. Contender grown in controlled environmental conditions, at either ambient or elevated (360 and 700 Î¼mol mol Ì„Â¹, respectively) COâ‚‚ concentrations ([COâ‚‚]), was monitored from 10 days after germination (DAG) until the onset of senescence. Elevated COâ‚‚ had a pronounced effect on total plant height (TPH), leaf area (LA), dry weight (DW) accumulation and specific leaf area (SLA). All of these were significantly increased by elevated [COâ‚‚] with the exception of SLA, which was significantly reduced. Except for higher initial relative growth rates (RGR) in COâ‚‚-enriched plants, RGR did not differ significantly between the two COâ‚‚ treatments throughout the remainder of growth period. While growth parameters clearly differed between COâ‚‚ treatments, the effects of COâ‚‚ on many physiological processes including net assimilation rate (NAR), Rubisco activity, and some foliar nutrient concentrations were largely transient. For example, COâ‚‚ enrichment significantly increased NAR, but from 20 DAG onward, NAR declined to levels measured on plants grown under ambient COâ‚‚. Similarly, the decline in both foliar N concentration and Rubisco activity in COâ‚‚-enriched plants after 20 DAG was significantly greater than the decline observed for ambient COâ‚‚ plants. Soluble leaf protein and total chlorophylls (a+b) were also significantly reduced in plants grown under elevated COâ‚‚. Chlorophyll (a/b) ratios increased with time underelevated COâ‚‚, indicating that the rate of decline of chlorophyll b was higher than that of chorophyll Î±. No significant changes in total carotenoid (x+c) levels were observed in either COâ‚‚ treatment. Under enhanced COâ‚‚, the foliar concentrations of K and Mn were increased significantly, while P, Ca, Fe and Zn were reduced significantly. However, changes in Mg and Cu concentrations were not significant. High COâ‚‚-grown plants also exhibited pronounced leaf discoloration or chlorosis, coupled with a significant reduction in leaf longevity. The levels of non-structural carbohydrates (sucrose, glucose, fructose and starch) and nitrogenous compounds (nitrogen, total soluble proteins and free amino acids) were determined for leaves and developing seeds of P. vulgaris. Leaf tissue of elevated COâ‚‚-grown plants accumulated significantly higher levels of both soluble sugars and starch. Leaf ultrastructure revealed considerable erilargement of starch grain sizes with surface areas more than five times larger compared to those of control plants. No apparent differences in structure and membrane integrity of chloroplasts in both COâ‚‚ treatments were noted. Although ambient COâ‚‚-grown plants had comparatively low levels of non-structural carbohydrates (NSC), they accumulated significantly higher levels of nitrogenous compounds. The levels of NSC were consistently higher in seeds of plants grown under elevated COâ‚‚. In comparison to plants grown at elevated [COâ‚‚], pods and seeds of ambient COâ‚‚-grown plants had significantly larger pools of free amino compounds and N. Stomatal conductance (gs) declined significantly, as expected for plants grown under elevated COâ‚‚. This was accompanied by a decline in transpiration rates (E). Reduced gs and E led to high AlE ratio, which meant improved water use efficiency (WUE) values for COâ‚‚-enriched bean plants. Leaf carbon isotope discrimination (âˆ†) against the heavier isotope of carbon (Â¹Â³C), has been used to select for high WUE in Câ‚ƒ plants. In plants grown at elevated COâ‚‚ concentration, ,1 was significantly reduced. Although âˆ† was negatively correlated with WUE in both COâ‚‚ treatments, the correlation was steeper and highly negative for COâ‚‚-enriched plants. These results indicate underlying differences in gas-exchange physiology, including stomatal responses between ambient and elevated COâ‚‚-grown plants. Photosynthetic acclimation was investigated using the response of assimilation to internal carbon dioxide concentration (A/Câ‚ curves). At early stages of growth, the initial slope of the A/Câ‚ response curve did not differ with COâ‚‚ treatment. In contrast, COâ‚‚-saturated photosynthetic rate (Amax) was significantly higher in plants grown under elevated versus ambient COâ‚‚ at 15 DAG. However, at subsequent stages of growth both the initial slope and Amax declined in bean plants grown in elevated COâ‚‚. Apparent carboxylation efficiency (ACE, estimated from the initial slope of A/Câ‚ response) values followed a similar trend and were significantly reduced in COâ‚‚-enriched plants. These results indicate that acclimation or negative adjustment of photosynthesis may have been caused by a combination of both stomatal and biochemical limitations. Bean plants grown under conditions of elevated atmospheric COâ‚‚ flowered 3 to 4 days earlier, and produced significantly more flowers and pods than plants grown at ambient conditions. Plants grown at elevated COâ‚‚ aborted 22 and 20% more flowers and pods, respectively, than plants grown at ambient COâ‚‚. Elevated COâ‚‚ also significantly increased the number of tillers or lateral branches produced by plants, which contributed to a significant increase in pod number and seed yield in these plants. Although plants grown at elevated COâ‚‚ produced on average 8 seeds per pod, while plants grown under ambient CO2 conditions produced 5 seeds per pod, the greater number of seeds was offset by lower seed weights in plants grown under _ elevated COâ‚‚. Thus, despite high seed yield in beans grown under elevated COâ‚‚, the harvest index (HI) did not change significantly between COâ‚‚ treatments.
Keywords: Plants -- Effect of carbon dioxide on; Kidney bean